The coexistence of asthma and COPD: some considerations about prevalence and lung function decline. Issue 3 (17th March 2022) - Marcon, Alessandro; Locatelli, Francesca; Accordini, Simone
With great interest we read the editorial by Mannino [1] regarding the investigation on the coexistence between asthma and COPD that we conducted using data from the population-based European Community Respiratory Health Survey (ECRHS) [2]. Mounting evidence suggests that FEV1 decline is slower among patients with COPD and asthma compared to those with COPD alone https://bit.ly/33NyoJq